Episode of Jinadatta Suri procuring texts hidden in the pillar - Temples of India Project Team (Jio Institute, 2024)
The twelfth oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) is the episode of Jinadatta Suri when he procured texts which were hidden in the pillar by a Jain ascetic several years ago. No one knew the location of the sacred scriptures, but the acharya (those who impart knowledge) could discern it using his magical powers. The pillar containing the sacred scriptures is depicted as a fluted column. This painting bears the name of the painter, M. Altaf Usta. The word ‘Usta’ used as a suffix here comes from the word ustad, meaning expert.